Activated platelet‐rich plasma improves cartilage regeneration using adipose stem cells encapsulated in a 3D alginate scaffold. (20th June 2018) - Beigi, Mohammad‐Hossein; Atefi, Atefeh; Ghanaei, Hamid‐Reza; Labbaf, Sheyda; Ejeian, Fatemeh; Nasr‐Esfahani, Mohammad‐Hossein
Abstract: In the current study, the effect of superimposing platelet‐rich plasma (PRP) on different culture mediums in a three‐dimensional alginate scaffold encapsulated with adipose‐derived mesenchymal stem cells for cartilage tissue repair is reported. The three‐dimensional alginate scaffolds with co‐administration of PRP and/or chondrogenic supplements had a significant effect on the differentiation of adipose mesenchymal stem cells into mature cartilage, as assessed by an evaluation of the expression of cartilage‐related markers of Sox9, collagen II, aggrecan and collagen, and glycosaminoglycan assays. For in vivo studies, following induction of osteochondral lesion in a rabbit model, a high degree of tissue regeneration in the alginate plus cell group (treated with PRP plus chondrogenic medium) compared with other groups of cell‐free alginate and untreated groups (control) were observed. After 8 weeks, in the alginate plus cell group, functional chondrocytes were observed, which produced immature matrix, and by 16 weeks, the matrix and hyaline‐like cartilage became completely homogeneous and integrated with the natural surrounding cartilage in the defect site. Similar effect was also observed in the subchondral bone. The cell‐free scaffolds formed fibrocartilage tissue, and the untreated group did not form a continuous cartilage over the defect by 16 weeks.